2018
DOI: 10.1016/j.virol.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus E2 protein is regulated by specific fibroblast growth factor receptors

Abstract: The papillomavirus (PV) E2 protein activates transcription and replication by recruiting cellular proteins and the E1 DNA helicase to their binding sites in the viral genome. We recently demonstrated that phosphorylation of tyrosine 102 in the bovine papillomavirus (BPV-1) E2 protein restricts these activities and that fibroblast growth factor receptor-3 (FGFR3) tyrosine kinase binds PV E2. Expression of FGFR3 decreased viral replication with both wild-type and the phenylalanine substitution at position 102, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…In contrast, another E2 interaction partner, FGFR2, reduced transient replication with Y138F ( Fig. 1C) (20). We previously reported that coexpression of the constitutively kinase-active FGFR3 K650E suppresses HPV-31 E1-and E2-mediated transient replication, so the Y138E result was consistent with this phenotype (12).…”
Section: Resultssupporting
confidence: 73%
“…In contrast, another E2 interaction partner, FGFR2, reduced transient replication with Y138F ( Fig. 1C) (20). We previously reported that coexpression of the constitutively kinase-active FGFR3 K650E suppresses HPV-31 E1-and E2-mediated transient replication, so the Y138E result was consistent with this phenotype (12).…”
Section: Resultssupporting
confidence: 73%
“…Of the 90 known tyrosine kinases, a consensus sequence is only recognized for LCK, Abl, Src, ALK, and EGFR (38). HPV-31 E2 Y102 fits the epidermal growth factor receptor (EGFR) consensus sequence, but our previous observations that E2 does not bind EGFR and that EGFR does not inhibit replication (40) imply that EGFR is not the kinase for Y102. The kinase that phosphorylates BPV-1 may differ from HPV-31, as the sequence flanking Y102 differs significantly (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The kinase which phosphorylates at position 102 has yet to be identified. We previously published that that the FGFRs associate with E2 (40,42), though none of these phosphorylate at Y102. Of the 90 known tyrosine kinases, a consensus sequence is only recognized for LCK, Abl, Src, ALK, and EGFR (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein phosphorylation is a reversible post-translational modification, often regulatory in nature, and is fundamental to cell signaling mechanisms. The HPV-8, HPV-11, HPV-16, HPV-31, bovine papillomavirus (BPV-1) and cottontail rabbit papillomavirus (CRPV) E2 proteins are phosphoproteins [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The first phosphorylations within E2 were identified on serine 298 and 301 residues, located in the non-conserved hinge region of BPV-1 E2, by peptide mapping and site-directed mutagenesis [ 16 ].…”
Section: Serine/threonine Phosphorylationmentioning
confidence: 99%